Correlation between general and abdominal obesity in diabetic and/or hypertensive active women (Research, Society and Development, 2020)
This study aimed to investigate the correlation between body mass index and anthropometric indicators of abdominal obesity in diabetic and/or hypertensive active patients of the Health Family Support Nucleus in Caninde, Ceará. It is a correlational research, transverse and quantitative analysis. The sample consisted of 25 diabetic and/or hypertensive women, mean age 63.64±10.25 years. The weight, height and waist circumference (WC) were collected. The body mass index (BMI) was calculated to identify general obesity and the abdominal obesity was identified based on WC indicators, waist/height ratio (WHR) and conicity index (CI). The results showed overweight patients (BMI = 28.3±4.0) and high anthropometric indexes of abdominal obesity (WC=100.1±8.7; WHR=66.4±5.1; CI=139.4±8.3). WC (p